2007
DOI: 10.1111/j.1365-2982.2007.00942.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NMDA receptor antagonists on visceromotor reflexes and on intestinal motility, in vivo

Abstract: Antagonists of NMDA receptors can inhibit both the transmission of pain signals from the intestine and enteric reflexes. However, it is unknown whether doses of the NMDA antagonist, ketamine, that are used in anaesthetic mixtures suppress motility reflexes and visceromotor responses (VMRs). In fact, whether intestinal motility is affected by NMDA receptor blockers in vivo has been little investigated. We studied the effects of ketamine and memantine, administered intravenously or intrathecally. Rats were maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…Subanesthetic doses of ketamine as CRI decreased the amplitude of duodenal contractions in horses a . This is in contrast to studies in other species in which low doses of ketamine did not affect intestinal motility 8,9 . In addition to its analgesic properties, ketamine has well‐documented anti‐inflammatory properties in several species.…”
contrasting
confidence: 96%
See 3 more Smart Citations
“…Subanesthetic doses of ketamine as CRI decreased the amplitude of duodenal contractions in horses a . This is in contrast to studies in other species in which low doses of ketamine did not affect intestinal motility 8,9 . In addition to its analgesic properties, ketamine has well‐documented anti‐inflammatory properties in several species.…”
contrasting
confidence: 96%
“…In addition, ketamine can have a direct inhibitory effect on gastrointestinal motility through antagonism of γ‐aminobutyric acid receptors in the enteric nervous system leading to decreased release of acetylcholine 18 . Low doses of ketamine to rats, dogs, and humans did not significantly affect gastrointestinal motility 8,9,19 . A single low dose of ketamine decreased duodenal migrating motor complex phase II (irregular muscle contractions) duration and prolonged phase I (period of quiescence) in pigs 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The involvement of CRF 1 in the maintenance of chronic stress-induced visceral hyperalgesia is supported by our observation that acute treatment with CP-154,526 normalized the VMR to CRD at a pressure of 40 mmHg (but not 60 mmHg), both these pressures being over the pain threshold level in healthy human subjects and rats (10,55). In previous studies with the use of a single stress session, we found that the same dose of CP-154,526 normalized stress-induced visceral hyperalgesia at distention pressures of both 40 and 60 mmHg (2,40,52,53).…”
Section: Discussionmentioning
confidence: 60%